Digital hybrid current mode control for DC–DC converters. Issue 4 (1st April 2019) - Ugur, Abdulkerim; Yilmaz, Murat
Abstract : A digital hybrid current mode (HCM) control technique which combines peak current and average current mode (ACM) control methods is studied. The proposed controller consists of three control loops, an analogue fast current loop, a digital slow current loop and an outer voltage loop. For the control method, both continuous and discrete‐time models are built. Similarly, a continuous‐time model for ACM control is provided for comparison. For both control techniques, a compensator design method is proposed. The control methods are implemented on a 6 W synchronous buck converter with a mixed‐signal ARM‐based microcontroller. Controller models are verified with the frequency response measurements of the inner and outer loops. In digital HCM control, higher DC gain and phase margin is achieved with the same gain margin compared to digital ACM control. Furthermore, the transient responses of the systems are analysed. When the outer voltage loop is open, 30% faster dynamic response is measured by the digital HCM method. With voltage compensation, comparable dynamic response on the output voltage is achieved without inductor current overshooting by the digital HCM control.